Curcumin attenuates renal interstitial fibrosis of obstructive nephropathy by suppressing epithelial-mesenchymal transition through inhibition of the TLR4/NF-кB and PI3K/AKT signalling pathways - Zhaohui Wang; Zhi Chen; Bingsheng Li; Bo Zhang; Yongchao Du; Yuhang Liu; Yao He; Xiang Chen (Taylor & Francis Group, 2020)
Context Renal interstitial fibrosis (RIF) is characterized by the accumulation of inflammatory cytokines and epithelial-mesenchymal transition (EMT). Curcumin exerts antifibrogenic, anti-inflammatory and antiproliferative effects. Objective To explore the mechanisms underlying the effects of curcumin on RIF. Materials and methods Eight-week-old male C57BL/6 mice were intragastrically administered curcumin (50 mg/kg/day) for 14 days after undergoing unilateral ureteral obstruction (UUO) operations. Renal function (blood urea nitrogen [BUN] and serum creatinine [Scr]) and inflammatory cytokine levels were tested using colorimetric assays and ELISA, respectively. EMT markers were evaluated through immunohistochemistry, western blotting and qPCR. Transforming growth factor beta 1 (TGF-β1; 10 ng/mL) and lipopolysaccharides (LPS; 100 ng/mL) were used to stimulate EMT and an inflammatory response in human renal proximal tubular epithelial (HK-2) cells, respectively, for further investigation. Results In vivo, curcumin significantly improved the levels of BUN and Scr by 28.7% and 21.3%, respectively. Moreover, curcumin reduced the levels of IL-6, IL-1β and TNF-α by 22.5%, 30.3% and 26.7%, respectively, and suppressed vimentin expression in UUO mice. In vitro, curcumin reduced the expression of vimentin and α-smooth muscle actin in TGF-β1-induced HK-2 cells. In LPS-induced HK-2 cells, curcumin decreased the release of IL-6, IL-1β and TNF-α by 43.4%, 38.1% and 28.3%, respectively. In addition, curcumin reduced the expression of TLR4, p-PI3K, p-AKT, p-NF- κB and p-IκBα in both LPS- and TGF-β1-induced HK-2 cells. Discussion and conclusions Curcumin repressed EMT and the inflammatory response by inhibiting the TLR4/NF-κB and PI3K/AKT pathways, demonstrating its potential utility in RIF treatment.